1999
DOI: 10.1046/j.1365-2222.1999.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective phosphodiesterase inhibitors for the treatment of bronchial asthma and chronic obstructive pulmonary disease

Abstract: Theophylline is commonly used in the treatment of obstructive airway diseases. The identification and functional characterization of different phosphodiesterase (PDE) isoenzymes has led to the development of various isoenzyme-selective inhibitors as potential anti-asthma drugs. Considering the distribution of isoenzymes in target tissues, with high activity of PDE3 and PDE4 in airway smooth muscle and inflammatory cells, selective inhibitors of these isoenzymes may add to the therapy of chronic airflow obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The PDEs are targets of highthroughput screening to find selective inhibitors for a variety of therapeutic purposes. Among these are to counter erectile dysfunction 1 (PDE5), asthma, and chronic obstructive pulmonary disease (COPD) via relaxation of smooth muscle cells [2][3][4] (PDE3, PDE4), to reduce inflammation associated with asthma and COPD [2][3][4] (PDE3, PDE4), to perform as cardiotonic agents to remedy congestive heart failure 5 (PDE3), and to act as cancer drugs by inducing apoptosis in neoplastic cells 6 (PDE2, PDE5). The human genome encodes 21 PDE genes categorized into 11 families, and each gene family has differing regulatory regions, substrate specificity, and binding affinities.…”
Section: Introductionmentioning
confidence: 99%
“…The PDEs are targets of highthroughput screening to find selective inhibitors for a variety of therapeutic purposes. Among these are to counter erectile dysfunction 1 (PDE5), asthma, and chronic obstructive pulmonary disease (COPD) via relaxation of smooth muscle cells [2][3][4] (PDE3, PDE4), to reduce inflammation associated with asthma and COPD [2][3][4] (PDE3, PDE4), to perform as cardiotonic agents to remedy congestive heart failure 5 (PDE3), and to act as cancer drugs by inducing apoptosis in neoplastic cells 6 (PDE2, PDE5). The human genome encodes 21 PDE genes categorized into 11 families, and each gene family has differing regulatory regions, substrate specificity, and binding affinities.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of PDE isoenzyme families have been identified, which have been classified according to their substrate affinities and specificities (cAMP versus cGMP), kinetic characteristics ( K m and V max ), subcellular distributions (soluble versus membrane-bound), and regulatory properties (e.g., activation by calcium/calmodulin (CaM)). During the past few years molecular biological methods have revealed an even higher complexity by the demonstration that most of these PDE families include more than one, and as many as four, distinct gene products (subtypes) as well as multiple splice variants within one gene family . Currently, major interest centers on selective inhibitors of PDE4, mainly due to the fact that PDE4 is the prominent isoenzyme present in inflammatory cells thought to be important in asthma and because inhibitors of PDE4 are effective in attenuating the activity of these inflammatory cells. PDE4 is also involved in the regulation of airway smooth muscle tone, together with PDE3, which is the major PDE present in airway smooth muscle. Consistent with the presence of large amounts of PDE3 and PDE4, studies with human isolated bronchi have demonstrated that selective inhibitors of either isoenzyme partially reverse spontaneous tone and elicit bronchorelaxation, , PDE3 inhibitors being somewhat more effective .…”
Section: Introductionmentioning
confidence: 99%
“…17 Currently, major interest centers on selective inhibitors of PDE4, [18][19][20] mainly due to the fact that PDE4 is the prominent isoenzyme present in inflammatory cells thought to be important in asthma [21][22][23] and because inhibitors of PDE4 are effective in attenuating the activity of these inflammatory cells. [24][25][26] PDE4 is also involved in the regulation of airway smooth muscle tone, together with PDE3, which is the major PDE present in airway smooth muscle. Consistent with the presence of large amounts of PDE3 and PDE4, studies with human isolated bronchi have demonstrated that selective inhibitors of either isoenzyme partially reverse spontaneous tone and elicit bronchorelaxation, 27,28 PDE3 inhibitors being somewhat more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Protein contains one or more heterologous amino acid sequences. At least one was specifically and indirectly interacting with cAMP, which shows an answer that regulates the interaction between the modified luciferase cAMP binding site and molecule (Schmidt et al, 1999). Means and strategies for in-vitro community commitment.…”
Section: List Of Abbreviationsmentioning
confidence: 98%
“…It is a glucagon-like hormone reaction system (Limbird, 2012). The cAMP signaling pathway plays a major role in many cellular responses, including cell formation, cell differentiation, cell proliferation, apoptosis, and metabolism (Spina et al, 2013). Cellular and systemic metabolic pathways are greatly affected by cAMP signaling.…”
Section: Synthesis Pathway Of Campmentioning
confidence: 99%